Identifying Opportunities and Barriers for Creating Environmental Health Education Standards of Practice Among Prenatal Healthcare Professionals - Watson-Leblanc, Kathryn (Université d'Ottawa / University of Ottawa, 2019)
Studies have reported that the most trusted health care relationship is that of the prenatal healthcare professionals (PHPs) and the prenatal patient. Yet many of the patient’s environmental health questions go unanswered for a variety of reasons. To better understand the situation, this research examines environmental health education practices of PHPs – obstetricians, prenatal nurses, family physicians, midwives and doulas - offered during the preconception and prenatal period. Specifically, this thesis discusses some of the PHP self-reported opportunities and barriers surrounding the provision of environmental health education (EHE). In person (n=17) and telephone (n=4) interviews were conducted with PHPs in the Ottawa Region. Additionally, a key informant within the Society of Obstetricians and Gynaecologists of Canada (SOGC) was asked specific questions about the association’s role in the development of standardized educational care guidelines. The results show that most PHPs have a limited knowledge of EHE and are reluctant to discuss it without access to more professional research. PHPs feel that there is little professional association support and that guidelines for adding EHE to their current prenatal care plans are non-existent. This study is one of the first studies that uniquely examined EHE in the prenatal period from perspective of prenatal healthcare professionals.
Keywords: prenatal health education; environmental health; prenatal care; practice guidelines